O PARFOR no Instituto Federal do Maranhão: a formação do professor de Matemática - VIEIRA, Fernanda Cristina Silva Gomes (2017)
This research is the result of many concerns about the field of teacher training in Mathematics. Teacher training, in service, through the National Plan for the Training of Teachers of Basic Education is a rich object of study, since schools, as spaces of instruction, education and training of subjects require multiple perspectives to understand The phenomena that are manifested in the educational universe. As a support for the theoretical discussions along with the information captured from the research subjects, we have contributions in the field of Educational Policy (MINAYO, 2012; GONZAGA, 2006; PIMENTA; GHEDIN; FRANCO, 2006). In this paper, we present the results of a study conducted in Brazil, in the field of research and development, In this paper, we present the results of the literature on the teaching of Mathematics in the teaching of Mathematics (Freitas, 2002, 2004, 2007, 2014 and Maúes, 2003, 2011, 2013, 2015) AMBROSIO, 1999, 2005, 2006, 2012). We developed a qualitative research, seeking to understand what the effects of the training in pedagogical practices were through the reports of the subjects that composed the Mathematics Degree Course / PARFOR, in the São Luís - Monte Castelo Campus. With the use of semi-structured interviews, we collected the empirical material with three student-teachers and three teachers who taught subjects at different times in the Course, in addition to having the collaboration of the PARFOR General Coordinator and the Course Coordinator. With the students-teachers who participated in this initial training, I was able to collect information about the effects of this training in the educational practice in the basic education school, from their point of view. I used the field diary to enrich and broaden the research data. The singularities seized in the narratives of the subjects investigated, in cross with our restlessness, composed the corpus of this research. The results point out conceptions and actions that make the teaching of mathematics in basic education schools, aligned in three categories of analysis: research, interdisciplinarity and contextualization